Coping Strategies, Psychological Well-Being and Problematic Internet Use During a Pandemic - Gerasimova A.A; Kholmogorova A.B (Moscow State University of Psychology and Education, 2020)
Pandemic and accompanying isolation period made significant changes in the daily activities of adolescents and young people. In the changed conditions, it is of interest to study the most adaptive coping strategies that contribute to the preservation of psychological well-being. The study involved 88 girls in Russia, aged 13 to 22 (M = 17.8; SD = 3).Data collection was carried out from 6 to 7 May 2020.The scales used were: Pandemic Lifestyle Changes Questionnaire, Generalized Problematic Internet Use Scale (GPIUS3), Loneliness Scale (UCLA), Satisfaction with Life Scale (SWLS), Well-Being Index (WHO-5), and Symptom Check List- 90-Revised (SCL-90-R).Short and long term planning was found to be positively associated with less depressive symptoms and greater life satisfaction. Social interaction and altruism are associated with lower rates of problematic Internet use. Family interaction is associated with indicators of psychological well-being and less loneliness. Family conflicts are correlated with an increase in rates of problematic Internet use and lower levels of psychological well-being.